Globalization and Smallholders : The Adoption, Diffusion, and Welfare Impact of Non-traditional Export Crops in Guatemala - Carletto, Calogero; Kirk, Angeli; Winters, Paul C.; Davis, Benjamin (2012)
This paper uses a duration analysis based on adoption data spanning 25 years from six communities in the Central Highlands of Guatemala to explore how household characteristics and external trends play into both the adoption and diffusion processes of non-traditional exports (NTX) among smallholders. Based on the analysis, NTX production appeared to have delivered less prosperity to adopters than initially promised. Smallholders may lack capacity to overcome difficulties that inevitably arise in complex types of cultivations and in highly variable global agricultural markets. Governmental and non-governmental organizations can attempt to mitigate these difficulties, but market forces may overwhelm these efforts.